Adherence to Vaccine Requirements among Hajj Pilgrims in Saudi Arabia, 2017-2019 - Adel Alotaibi; Sami S Almudarra; Homoud S Algarni; Yasser Bakhsh; Zahir Mohamed Elamin Dafaalla; Nada Abdulaziz Alhowail; Abdulla M Assiri (Tropical Health and Medical Research, 2021)
Hajj pilgrims must have certain vaccines for pilgrimage; these requirements aim to reduce the spread of infectious diseases. This study analyzed the trends in vaccine adherence for meningitis, yellow fever, and polio from January 2017- December 2019. These trends can help in guiding future policymaking to prevent outbreaks during Hajj and similar mass gatherings. We analyzed data using descriptive statistics for Hajj pilgrims and Hajj seasonal workers arriving in Saudi Arabia over three years (2017–2019). Health Control Centers (HCCs) collected data at points-of-entry (PoE) and entered it into Saudi Arabia’s Health Electronic Surveillance Network (HESN). We reviewed HESN data to collect information on total passengers arriving per country and the number of passengers vaccinated for: meningococcal meningitis, poliomyelitis, and yellow fever. We compared data to identify the difference in vaccination by region.  We used chi-square tests to assess differences in compliance rate among these travelers by year and country of origin. The number of participating countries increased from 113 to 132. Meningitis vaccine coverage increased by 5% from 2017–2019. The increase was not statistically significant. Asia had the lowest overall adherence rate (83%). Yellow fever adherence decreased significantly using a difference of mean adherence between 2017 and 2019 (p-value 0.01). Polio vaccination adherence decreased by 5% from 2017 to 2019; this was not significant (p-value = 0.08). The vaccine coverage increased for meningitis and decreased for yellow fever and polio. Less than 100% vaccine adherence among Hajj travelers creates the potential for the spread of infectious diseases. Proof of vaccination should be required in submitted visa applications. Countries of origin and Saudi Arabia must work together to ensure that all Hajjis are adequately vaccinated before departure.